ANALISIS PENGARUH ANGKA HARAPAN HIDUP, RATA-RATA LAMA SEKOLAH, TINGKAT KEMISKINAN TERHADAP KESEJAHTERAAN PADA KABUPATEN/KOTA DI PROVINSI BALI - Putra Kusuma, I Made Cahyadi; Bendesa, I.K. G. (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 11 (2022): vol.11.11. NOVEMBER 2022[4011-4233], 2022)
Well-being is an aggregate condition of individual satisfaction. The province of Bali has a very unique economic structure compared to other provinces in Indonesia. This uniqueness is due to the fact that most of the community's sources of livelihood come from the tertiary sector (tourism) while other sectors only act as supporting sectors. Many factors affect the welfare of districts/cities in Bali Province. The purpose of this study was to analyze the effect of life expectancy, average length of schooling, and poverty simultaneously and partially on welfare in districts/cities in Bali Province. This study uses an associative quantitative approach which is located in the province of Bali which covers nine districts/cities. The data used is secondary data obtained from the Central Statistics Agency of Bali Province from 2010-2021 in 9 districts/cities so that the number of observations is 108 years. The method of data collection in this study is the non-participant observation method. The analysis technique used is multiple linear regression analysis. The results of the study show that (1) life expectancy, average length of schooling, and poverty level simultaneously affect the welfare of districts/cities in Bali Province, (2) life expectancy and average length of schooling partially have positive and negative effects. significant effect on welfare, while the poverty level partially has a negative and significant effect on welfare in regencies/cities in Bali Province.